Common Values in the Community of a Shared Future: A Case Study of Othello - Xu, Xinwen; Yang, Xue; Huang, Chi (International Journal of Social Sciences and Public Administration, 2024)
William Shakespeare, known as the "Zeus on Mount Olympus of human literature", has created a vast cultural treasure trove and a valuable spiritual heritage for the later generations. Taking Othello, one of Shakespeare's four great tragedies, as an example, this paper conducts a research on the social concepts such as racial discrimination, stereotyped thinking, human morality and other related issues in this work, and explores the common values reflected therein. Based on the research, this paper draws the conclusion that even under different ideologies, all countries in the world should bear the responsibility of building a community with a shared future for mankind.